2020
DOI: 10.18488/journal.35.2020.72.118.129
|View full text |Cite
|
Sign up to set email alerts
|

Role of Talent Development on Talent Engagement and Self-Efficacy: A Structural Model

Abstract: The purpose of this research is to examine the influence of talent development (TD) on talent engagement (TE) and self-efficacy (SE). Data were collected through a questionnaire from the trainees of Bangladesh Institute of Human Resource Management (BIHRM). Two hypotheses were developed and tested on the collected data. Structural equation modeling (SEM) is performed which includes both measurement model and structural model. Average variance extracted (AVE), Cronbach's alpha (α), composite reliability (CR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…positive and significant influence, indicating that the better and higher the talent management is done, the more the self-efficacy will increase and be better too. The results of this study support previous research conducted by Ali et al, (2020), where there is a positive and significant effect of talent management on self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…positive and significant influence, indicating that the better and higher the talent management is done, the more the self-efficacy will increase and be better too. The results of this study support previous research conducted by Ali et al, (2020), where there is a positive and significant effect of talent management on self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…The results endorsed the mediating effect of talent development in the relationship between transactional leadership and talent engagement, which is consistent with the study by Turan (2021). Since transactional leaders can influence their subordinates for their development (Masa'deh et al., 2016) and talent development directly impacts engagement (Ali et al., 2020), so the current results stressed the mediating role of talent development in the association between transactional leadership and talent engagement. In this context, transactional leaders regularly arrange development programs to create opportunities for employees to learn and apply, which in turn, influence employees’ self‐efficacy to motivate them to demonstrate a higher level of engagement.…”
Section: Discussionmentioning
confidence: 64%
“…Ali et al. (2020) found that talent development plays a significant role in enhancing the level of engagement and self‐efficacy of talents. Marrybeth et al.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…(Isa et al, 2018) described talent development as a social process aims at acquiring and sharing necessary information that influence the experience development of talents within an organization. By retaining talents, development can benefit organization as it reduces the costs associated with recruitment of new employees and operational costs (Ali et al, 2020).…”
Section: Talent Management Dimensions (Strategies)mentioning
confidence: 99%